Consumer Legal Protection in Online Transactions: Challenges and Opportunities in Indonesia's Digital Economy - Dzuhriyan, Ahmad Refi; Permana, Surya Indra; Gufron, M. Khaidir Ali (Justice Voice, 2024)
This study examines the legal protection of consumers in online business transactions in Indonesia, an issue that has become increasingly critical in the digital era. Advances in information technology have transformed traditional commerce into e-commerce, offering convenience while also introducing various risks, such as fraud, product non-conformity, and breaches of consumer data privacy. Employing a normative juridical method with a statutory approach, this research analyzes the implementation of Law No. 8 of 1999 on Consumer Protection and the Electronic Information and Transactions Law (ITE Law) in resolving e-commerce disputes. The findings reveal that despite the existence of legal regulations, significant challenges persist in the implementation of consumer protection, primarily due to low consumer awareness of their rights and weak law enforcement. The novelty of this study, compared to previous research, lies in its empirical approach to identifying the legal challenges consumers face in online transactions. In addition to examining existing regulations, this study investigates real cases of e-commerce fraud in Indonesia that have led to financial losses for consumers. The study underscores the importance of consumer education, stricter supervision of online business operators, and the development of more effective dispute resolution mechanisms. By highlighting the necessity of synergy between the government, business operators, and society, this research contributes to the formulation of more adaptive policies to strengthen consumer protection in the digital economy.